Comparative studies between vegetables oils and mineral oil as alternative to power transformer insulation oil / \c Aimi Athirah Hazwani binti Zaidi. - Aimi Athirah Hazwani Zaidi (School of Electrical System Engineering, Universiti Malaysia Perlis, 2017)
The objectives of this research are ; to identify the best type of vegetable oils suitable to be used for power transformer ; to analyze the electrical and physical properties of the vegetable oils before and after being applied to the transformer ; to evaluate the transformer performance when using the vegetable oils as the insulation oil.